Influencia del juzgado de familia y las partes procesales en la eficacia de las medidas de protección dictadas, Trujillo 2020 - Tapia Tasso, Laura Alexandra (2023)
The present investigation had the objective of determining the influence of the resolutions of the Ninth Family Court of the Superior Court of Justice of La Libertad and the actions of the procedural parties in the effectiveness of the protection measures issued by said court. To do this, the technique of recording and documentary analysis was used, in addition to the analytical-synthetic, inductive-deductive and exegetical method, in order to analyze twenty (20) files on family violence filed in the Ninth Family Court of the Superior Court of Justice of La Libertad during the year 2020, in which protective measures were issued in favor of the victim and at least one new complaint was added to the file for repeated acts of violence between the parties. The results show that the resolutions of the Ninth Family Court of the Superior Court of Justice of La Libertad and the actions of the procedural parties have a negative influence on the effectiveness of the protection measures issued, while actions or omissions are identified that prevent their main purpose is fulfilled, which is to neutralize or minimize the harmful effects of the violence exerted against the victim.